Pelayanan Prima dalam Pendidikan: Tinjauan Sistematis Tentang Strategi Meningkatkan Kepuasan Pelanggan dan Mutu Layanan - Umamul Muslikhin; St. Nur Azizah; Muhammad Taufiq Hidayatullah; Mu’alimin Mu’alimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Service excellence has become a strategic issue in modern educational management because it is directly related to service quality, customer satisfaction, and the image of educational institutions. In the context of global competition and demands for public transparency, educational institutions are required to provide services that are effective, efficient, and oriented to the needs of students and the community. This study aims to systematically examine how the concept of service excellence is implemented in educational institutions and its impact on customer satisfaction. The method used was a systematic literature review, searching articles in national databases such as Google Scholar, Garuda, and campus journal portals using the keywords